Human kidney-derived cells ameliorate acute kidney injury without engrafting into renal tissue - Santeramo, Ilaria; Herrera Pérez, Zeneida; Gretz, Norbert (Stem cells translational medicine, 2017)
Previous studies have suggested that CD133+ cells isolated from human kidney biopsies have the potential to ameliorate injury following intravenous (IV) administration in rodent models of kidney disease by integrating into damaged renal tissue and generating specialized renal cells. However, whether renal engraftment of CD133+ cells is a prerequisite for ameliorating injury has not yet been unequivocally resolved. Here, we have established a cisplatin‐induced nephropathy model in immunodeficient rats to assess the efficacy of CD133+ human kidney cells in restoring renal health, and to determine the fate of these cells after systemic administration. Specifically, following IV administration, we evaluated the impact of the CD133+ cells on renal function by undertaking longitudinal measurements of the glomerular filtration rate using a novel transcutaneous device. Using histological assays, we assessed whether the human kidney cells could promote renal regeneration, and if this was related to their ability to integrate into the damaged kidneys. Our results show that both CD133+ and CD133− cells improve renal function and promote renal regeneration to a similar degree. However, this was not associated with engraftment of the cells into the kidneys. Instead, after IV administration, both cell types were exclusively located in the lungs, and had disappeared by 24 hours. Our data therefore indicate that renal repair is not mediated by CD133+ cells homing to the kidneys and generating specialized renal cells. Instead, renal repair is likely to be mediated by paracrine or endocrine factors. Stem Cells Translational Medicine